Denitrobaculum tricleocarpae gen. nov., sp. nov., a marine bacterium from coralline algae Tricleocarpa sp. Issue 5 (28th April 2020) - Wang, Guanghua; Tang, Dahao; Li, Guangyu; Xu, Shuailiang; Dang, Ge; Su, Hongfei; Liao, Zhiheng; Chen, Biao; Huang, Wen; Liang, Jiayuan; Yu, Kefu
Abstract : A Gram-stain-negative, non-spore-forming, aerobic, motile, curved rod-shaped bacterium, designed strain R148 T was isolated from a coralline algae Tricleocarpa sp. collected from Weizhou island, PR China. The optimal growth of R148 T occurred at 25 °C, pH 8–9 in the presence of 0.5 % (w/v) NaCl on the basis of amended marine broth 2216. The genomic DNA G+C content was 59.5 mol%. The only detected respiratory quinone was Q-10. The major polar lipids were phosphatidylmethylethanolamine, phosphatidylglycerol, diphosphatidylglycerol, phosphatidylethanolamine, and three unidentified ninhydrin-positive lipids. The major cellular fatty acids were C18 : 1 ω7 c, C16 : 1 ω7 c, C19 : 0 cyclo 9, 10 DMA and C18 : 0 . The results of 16S rRNA gene-based global alignment indicated that the closest neighbour of strain R148 T was Pelagibius litoralis DSM 21314 T (93.1 % similarity), the second is Limibacillus halophilus KCTC 42420 T (92.2 %). The results of phylogenetic analysis indicated that R148 T forms a distinct branch in the robust clade of R148 T and P. litoralis DSM 21314 T, while the taxonomic position of this clade in the family Rhodospirillaceae is ambiguous among phylogenetic approaches. The low 16S rRNA gene similarity and distinct polar lipid and cellular fatty acid profile could readily distinguish R148 T from closely related type strains. So R148 T is suggested to represent a novel species in a novel genus, for which the name Denitrobaculum tricleocarpae gen. nov., sp. nov. is proposed. The type strain is R148 T (=MCCC 1K03781 T =KCTC 72137 T ).